Influencing culture related risks to improve project success - Wilson, Arthur; Carey, Brad; Buckley, Amma (2023)
Advances in technologies have resulted in significant interest, projects and investment in associated infrastructure to transform how public and private organisations engage and interact with their stakeholders. However, the success of such projects is far from certain. Projects continue to fail in higher numbers than they succeed across multiple industries, no matter the type of project management methodology adopted. Project success is often focused on time, cost and quality. However, there is growing recognition that the dynamic interaction of multiple actors from diverse networks influences project success. Current project management methodologies may not sufficiently reflect the complex and dynamic nature of projects. This paper explores how actions to influence culture can contribute to project success. We explore this concept through the lens of actor-network theory (ANT) which was used to guide the collection of data and the data analysis.